Two-pot synthesis and photophysical studies of 1, 6-disubstituted 5-aza-indoles from succinaldehyde and N-aryl propargylic-imines. Issue 48 (3rd December 2021) - Vanaparthi, Satheeshvarma; Mamta; Yadav, Jyothi; Pawar, Amol Prakash; Iype, Eldhose; Rana, Sravendra; Kumar, Indresh
Abstract : A straightforward two-pot method is developed to prepare a series of 2-alkynyl-pyrrole-3-aldehydes, initially from succinaldehyde and N -aryl propargylic-imines, followed by Ag-catalyzed 6- endo-dig -cyclization to obtain 1, 6-disubstituted 5-aza-indoles in good yields. Abstract : A two-pot synthesis of 5-aza-indoles has been developed from aqueous succinaldehyde and N -aryl propargylic-imines. This overall protocol involves: (i) the metal-free [3 + 2] annulation of aqueous succinaldehyde and N -aryl propargylic-imines to access 2-alkynyl-pyrrole-3-aldehydes and (ii) Ag-catalyzed 6- endo-dig -cyclization to obtain substituted 5-aza-indoles in the second pot. The 5-aza-indoles showed engaging photophysical activities, and the practicality of this pot-economic gram-scale synthesis has been demonstrated.